Clinical outcome following primary total hip or knee replacement in nonagenarians - Skinner, D (Ann R Coll Surg Engl, 2016)
INTRODUCTION: The Elective Orthopaedic Centre in Epsom has an established patient reported outcome measures programme, into which all patients are enrolled. Postoperative complications, Oxford hip/knee scores (OHS/OKS) and EQ-5D™ (EuroQol, Rotterdam, Netherlands) scores are collected up to the second postoperative year. Our population is ageing and the number of joint replacements being performed on the very elderly is rising. The aim of this study was to investigate the outcome of joint replacements in a nonagenarian population. METHODS: Our dataset was reviewed retrospectively for a cohort of nonagenarians undergoing either a primary total hip replacement (THR) or total knee replacement (TKR) between April 2008 and October 2011. Postoperative complications, mortality rates and functional outcomes were compared with those of a time matched 70–79-year-old cohort. RESULTS: Nonagenarians requiring a THR presented with a lower preoperative OHS (p=0.020) but made a greater improvement in the first postoperative year than the younger cohort (p=0.040). The preoperative OKS was lower for nonagenarians than for the control group (p=0.022). At one and two years after TKR, however, there was no significant difference between the age groups. The nonagenarians had a greater risk of requiring a blood transfusion following both THR (p=0.027; 95% confidence interval [CI]: 1.11–5.75) and TKR (p=0.037; 95% CI: 1.08–16.65) while the latter cohort also required a longer stay than their younger counterparts (p=0.001). Mortality rates were higher in the nonagenarian group but these were in keeping with the life expectancy projections identified by the Office for National Statistics. CONCLUSIONS: Over a two-year period, the functional outcome and satisfaction rates achieved by nonagenarians following a THR or TKR are comparable with 70–79-year-olds.